Proteinograma do soro lácteo de ovelhas da raça santa inês em diferentes fases de lactação - Lemos, Vânia F.; Guaraná, Eduardo L.S.; Afonso, José A.B.; Fagliari, José J. [UNESP]; Silva, Paulo [UNESP]; Soares, Pierre C.; Mendonça, Carla L. (FapUNIFESP (SciELO), 2013)
This study aimed to evaluate the influence of lactation phases on the proteinogram of whey protein in Santa Inês ewes. Ewes were accompanied in a semi-intensive system using the same sanitary and nutritional management evaluated at 15, 30, 60 and 90 days postpartum (end of weaning and lactation). Clinical examination of the mammary gland was carried out through and bacteriological culture. The screening of the material resulted in 44 milk samples of healthy glands concurrent negative by CMT and bacteriological culture exam. For obtaining the whey protein renin solution was used. The whey was fractionated into aliquots and kept in the -80C freezer to later separation of protein fractions. For determination of total protein of whey protein was employed the biuret, observing the linearity of the test. Separation of protein fractions was performed, using polyacrylamide gel containing sodium dodecyl sulfate (SDS-PAGE). Eigth protein were observed including lactoferrin, serum albumin, IgA, IgG (heavy chain IgG (IgG CP), light chain IgG (IgG CL), ß-lactoglobulin, a-lactalbumin and proteins identified as PM 15000 and PM 29000. No significant difference was observed at different stages of lactation in the following protein: IgA (P>0.3895), lactoferrin (P>0.1611), PM 29000 (P>0.4879), α-lactalbumin (P>0.0799) and PM15000 (P>0.4494). In total protein (P<0.0022), albumin protein (P<0.0377) and IgG (P<0.0354) it was observed a significant variation in the first moments of observations, in the ß-lactoglobulin protein (P<0.0005) there was significant variation with reduction of 15 to 30 days postpartum with progressive elevation until the last stage of lactation (90 days postpartum). The SDS-PAGE technique allowed the quantification of eigth whey proteins in health ewes. The protein fractions identified reflect the profile of whey to ovine species, with influence of stages of lactation in albumin, IgG and ß-lactoglobulin.
Proteinogram the whey protein of Santa Ines sheep breed in different stages of lactation
Keywords: Lactation; Milk; Postpartum; Proteinogram; SDS-PAGE; Small ruminants; Whey protein